2017
DOI: 10.1111/jac.12244
|View full text |Cite
|
Sign up to set email alerts
|

Waterlogging events during stem elongation or flowering affect yield of oilseed rape (Brassica napus L.) but not seed quality

Abstract: Oilseed rape suffers from serious waterlogging in many regions of the world limiting the cultivation area for rapeseed. Due to the man‐induced climate change, the risk of severe waterlogging events and associated therewith the damage of rapeseed plants will increase, even in Europe and North America. To investigate the effects of waterlogging on growth, yield and seed quality, rapeseed was cultivated throughout its vegetation period and waterlogged for 14 days at two different growth stages: at stem elongation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 40 publications
5
27
0
Order By: Relevance
“…www.nature.com/scientificreports www.nature.com/scientificreports/ serious physiological constraint and there is a significant relationship between yield and growth of plant during this stage 39 . Previous studies showed that waterlogging after flowering stage significantly reduced the 1000-grain weight and dry matter quality of rapeseed, among which the dry matter quality decreased by 25.6%, and the 1000-grain weight decreased by 12.3% 29 .…”
Section: Discussionmentioning
confidence: 99%
“…www.nature.com/scientificreports www.nature.com/scientificreports/ serious physiological constraint and there is a significant relationship between yield and growth of plant during this stage 39 . Previous studies showed that waterlogging after flowering stage significantly reduced the 1000-grain weight and dry matter quality of rapeseed, among which the dry matter quality decreased by 25.6%, and the 1000-grain weight decreased by 12.3% 29 .…”
Section: Discussionmentioning
confidence: 99%
“…In the context of climate change, an increased frequency of waterlogging has been observed worldwide, which has an especially detrimental effect on crop production [ 10 , 46 ]; prolonged seasonal rainfall often causes severe yield losses of grapevine in central and southern China. To endure waterlogging stress, a series of rapid and profound molecular and metabolic responses will unavoidably be activated.…”
Section: Discussionmentioning
confidence: 99%
“…60%-75% of controls in 4-leaf plants at stem elongation) than when at late stages (ca. 70%-85% of controls in seed filling/bud appearance) (Gutierrez Boem, Lavado, & Porcelli, 1996;Wollmer, Pitann, & Mühling, 2018). The main affected component in rapeseed, irrespective of the time/age of waterlogging occurrence, was the number of siliques per plant (Gutierrez Boem et al, 1996;Zhou, Zhao, & Lin, 1997).…”
Section: Introductionmentioning
confidence: 99%